Visual ecology: social, aesthetic and ergonomic aspects of graphic interface design - Avgul Matvey E. (Архитектон, 2025)
The article considers the evolution of visual ecology problems in interdisciplinary scientific research and changes in the content of the concept of "visual ecology" in the context of intervention of digital environment in everyday human activities. Problems of visual overloading of pages with information at the early stages of graphical interface design are identified. An analysis of a large database of modern digital products revealed key factors of environmentally friendly design of graphical interfaces. Conclusions are made that the environmental friendliness of a product is becoming one of the key formal features of modern design, and taking into account the requirements of visual ecology determines both the social and aesthetic aspects of design.